Tinjauan Yuridis Terhadap Over Credit (Pengalihan Utang) Dalam Perjanjian Leasing Kendaraan Mobil di PT Toyota Astra Financial - Imas Febrianto; Indra Rahmatullah (JOURNAL of LEGAL RESEARCH, 2019)
AbstractIn the overcredit agreement under the hand on the vehicle, the car caused a loss both from the leasing party and the parties who took the action. In fact, the leasing financing agreement prohibits the action stated in the clause.This study examines the legality of overcredit within the scope of Civil Law in Indonesia. Then the researcher explained the right stages in overcrediting car vehicles officially according to the SOP (Standard Operating Procedure) on leasing PT. Toyota Astra Financial. In addition, the research study examined the legal consequences of overcrediting under the hands of car vehicles in a philosophical, juridical, and sociological perspective.The results of the study show that due to the law of overcrediting under the hands of car vehicles in terms of philosophical contradiction with the Contracted Justice Theory proposed by John Rawls. The act of overcrediting under the juridical aspect can also have a negative impact by paying compensation to the leasing party in accordance with the Civil Code Article 1243, Article 1266, and Article 1267 due to default (broken promise). Then, overcredit under the hand can also end in court as in the case of Decision Number 10 / Pdt.G / 2017 / PN.Rkb.Keywords: Due to Law, Under Hands, Overcredit, Leasing Agreement